Analyzing the Classical and Chandler’s Conceptions of the Cost Theory in the Long Run - Klymova Svitlana O.; Yatsyna Viktoriia V. (Bìznes Inform, 2023)
The aim of the article is to study both the classical and Chandler’s conceptions regarding the cost theory in the long run and determine their differences. Proceeding from the current realities of increasing the role of new technologies and their impact on the competitiveness of enterprises, the article proves the need to introduce a new type of costs – «one-time» costs. The innovative essence of these costs is disclosed, which makes it possible to consider one-time costs as those that correspond to the intensive direction of expansion of production, as well as to separate them from conditionally fixed and variable costs. The possibility of the impact of one-time costs (as costs associated with the acquisition or development of new technologies) on the scale effect is also considered. It is proved that it is the distribution of one-time costs on the volume of production that allows the enterprise to achieve a positive scale effect much faster and minimize its costs. It is shown that the synergistic effect is an important component in strategic management and business development, but it can also be negative in the case when the interaction of factors leads to a negative impact or increases undesirable consequences. The article notes the reason for the absence of a negative scale effect in the Chandler’s conception, which explains the desire of many enterprises to merge. This desire is also explained by the existence of fixed and variable costs in the long run in Chandler’s conception, in contrast to the classical theory, where there are only variable costs in the long run. The possibility of further determining and applying the optimal structure and rate of change of one-time and conditionally fixed costs per unit of production in order to improve the efficiency of production and competitiveness of enterprises is considered.